2012
DOI: 10.1103/physrevlett.108.067402
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Covalent Bonding in Liquid Silicon Probed by Inelastic X-Ray Scattering

Abstract: Metallic liquid silicon at 1787K is investigated using x-ray Compton scattering. An excellent agreement is found between the measurements and the corresponding Car-Parrinello molecular dynamics simulations. Our results show persistence of covalent bonding in liquid silicon and provide support for the occurrence of theoretically predicted liquid-liquid phase transition in supercooled liquid states. The population of covalent bond pairs in liquid silicon is estimated to be 17% via a maximally-localized Wannier f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…The expressions presented here would allow the average cyclotron mass over the whole Fermi surface to be approximated from a limited set of temperature-dependencies 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 measured with the applied magnetic field along some small number of SDs. We also note some recent experimental work on the melting of the crystalline state, and point out that the averaging process would be applicable to liquid metals [ 54,55] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expressions presented here would allow the average cyclotron mass over the whole Fermi surface to be approximated from a limited set of temperature-dependencies 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 measured with the applied magnetic field along some small number of SDs. We also note some recent experimental work on the melting of the crystalline state, and point out that the averaging process would be applicable to liquid metals [ 54,55] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43...…”
Section: Discussionmentioning
confidence: 99%
“…(7 -9) (left) and 1-, 2-and 3-SDs (right), determined, respectively, by ϕ=15 0 and by positive zeros of P 2 (cosΘ), P 4 (cosΘ) and P 6 (cosΘ) with Θ equals, respectively: 54 Fig. 7), facilitating the inclusion of the first five harmonics in Eq.…”
Section: Figmentioning
confidence: 99%
“…It was proved another time that pressure has an essential role in the production and control of superconductivity (Sun et al, 2012): it is reported that in the superconducting iron chalcogenides, a second superconducting phase suddenly re-emerges at a critical temperature Tc reaching 48.0 K and above 11.5 GPa, after the Tc drops from the first maximum of 32 K at 1 GPa. Metallic liquid silicon at 1787 K was investigated using X-ray scattering (Okada et al, 2012): the results show persistence of covalent bonding in liquid silicon and provide support for the occurrence of theoretically predicted liquid-liquid phase transition in supercooled states. To finish, it can be pointed out the crystallographic structure refinement of a protein, PthXo1 (which is a transcription activator-like, TAL, effector), encoded by an important group of harmful plant pathogens (Mak et al, 2012): understanding DNA recognition by TAL effectors may facilitate rational design of DNA-binding proteins with biotechnological applications.…”
Section: Why Using Large Scale Facilities In Extreme Crystallography?mentioning
confidence: 99%
“…In order to hold the sample without contamination, a high temperature electrostatic levitator (HTESL) was used [23]. The detail of the HTESL for SPring-8 experiments is described in [24]. A polycrystalline sample (β-B, 99.9% purity) was used to obtain a spherical averaging Compton profile.…”
mentioning
confidence: 99%
“…The energy spectrum of Compton scattered X-rays was converted to the Compton profile with a momentum resolution of 0.16 a.u. The data processing to deduce the Compton profile from the raw energy spectrum consists of following steps: background subtraction, energy dependent corrections for the Compton scattering cross section, the absorption of incident and scattered x-rays in the sample, consideration of efficiency of the analyzer and the detector, and corrections for double scattering events: see [22]. Background in the measured profile is suppressed in the levitation technique used since no material is present in the immediate vicinity of the sample at the x-ray scattering center.…”
mentioning
confidence: 99%